2016
DOI: 10.1155/2016/4591910
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform Biomarker Discovery for Bladder Cancer Recurrence Diagnosis

Abstract: Purpose. Nonmuscle invasive bladder cancer (BCa) has a high recurrence rate requiring lifelong surveillance. Urinary biomarkers are promising as simple alternatives to cystoscopy for the diagnosis of recurrent bladder cancer. However, no single marker can achieve the required accuracy. The purpose of this study was to select a multiparameter panel, comprising urinary biomarkers and clinical parameters, for BCa recurrence diagnosis. Experimental Design. Candidate biomarkers were measured in urine samples of BCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In a recent study, De Paoli et al [95] analyzed the potential of multiple biomarkers (including HER2) for BC recurrence diagnosis on urine samples from NMIBC patients. Since no single biomarker candidate achieved an acceptable performance by itself, the authors identified several multivariable regression models; the best performing one (area under the curve 0.91) comprised both clinical (number of past recurrences, number of BCG therapies, stage at time of diagnosis) and molecular parameters, including HER2, which yielded the highest area under the curve value (0.7305) by itself.…”
Section: Survivalmentioning
confidence: 99%
“…In a recent study, De Paoli et al [95] analyzed the potential of multiple biomarkers (including HER2) for BC recurrence diagnosis on urine samples from NMIBC patients. Since no single biomarker candidate achieved an acceptable performance by itself, the authors identified several multivariable regression models; the best performing one (area under the curve 0.91) comprised both clinical (number of past recurrences, number of BCG therapies, stage at time of diagnosis) and molecular parameters, including HER2, which yielded the highest area under the curve value (0.7305) by itself.…”
Section: Survivalmentioning
confidence: 99%
“…Next, for each of this cancer associated processes biomarkers representing them were selected. Multiplexed assays for the panel were established in urine on a conventional microarray platform with fluorescence detection [ 83 ], and then transferred to a microtiter plate format enabling the easy automation of the developed multiplexed high-throughput assays and cost efficient colorimetric detection (see Figure 5 ) [ 119 ]. From an initial panel of 23 potential biomarkers, for seven no reagents in sufficient high quality were found, and those potential candidates had to be removed from the panel.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers reported that HER2 positivity may predict muscle invasion in urothelial cancer of the urinary bladder (33,34,35). Based on previous studies regarding HER2 involvement in tumor progression from bladder cancer, this oncoprotein was included in newly designed multiplatform biomarkers designed to be used in clinical practice to predict invasion and reccurence in patients with urothelial cancer (36,37,38). Our data support the HER2 role in the local invasion of urothelial tumors, most of the cases scored as +2 and +3 being staged into T3 (a or b) group.…”
Section: Discussionmentioning
confidence: 99%